Uji Kinerja Mesin Pencacah Tipe Multiguna untuk Pencacahan Tongkol Jagung - Aprilliandi, Reza; Suharyatun, Siti; Oktafri, Oktafri; Haryanto, Agus (Jurnal Agricultural Biosystem Engineering, 2022)
Indonesia is an agrarian country because it has abundant agricultural products, one of its mainstay is corn. Besides rice, corn is one of the staple foods consumed by Indonesian people, but only the corn’s grain are used in corn. The cornhusk and corn cobs are usually thrown away or just burned because they are not used. One of the way to process corncobs waste is by chopped corncobs to be used as animal feed. Corncobs that have been separated from the grains of corn were chopped using a chopper machine (Chopper). All this time, these machines have been widely used by society. However, it still raises problems related to the chopper machine. This study uses the observed parameters, namely the enumeration work capacity, fuel consumption, the uniformity of the enumeration results, and the yield. Based on the result of the study, the effect of treatment on yield was not significantly different, with an average yield value of 94.89%. The highest chopping results of corn cobs is at high rotational speed of 1245 rpm with an engine working capacity of 332.88 kg/hour. The lowest fuel consumption is at a rotating speed of 890 rpm with a fuel requirement of 0.74 liters/hour. The effect of treatment on the distribution of chopped results was not significantly different, with the average value for fine chopping 67.29% and 32.71% for coarse chopping. Based on the ANOVA test, the effect of treatment on fuel productivity was not significantly different, with an average fuel productivity value of 301.61 kg/liter. Keywords: Chopper, Chopper Machine, Corn, Corncobs, Rotating Speed.